1989
DOI: 10.1017/s0022149x00009160
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism inTrichuris globulosa(Nematoda)

Abstract: Adult males and females ofTrichuris globulosa, an intestinal nematode parasite of goats, were studied for their lipid composition, capability of incorporation of (Na)-1-14C-acetate into different lipid classes and the activity of certain key enzymes of lipid metabolism. The parasite possesses a large variety of lipids including certain complex lipids. These are phosphatidylcholine (PC), diphosphatidylglycerol (cardiolipin), lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), phosphatidylserine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Thus, specific functions were identified that may differ between intestinal tissues of the sexes. From whole worm studies, female worm associated lipid transport functions were also reported in Trichuris globulosa (Sarwal et al 1989). …”
Section: Discussionmentioning
confidence: 98%
“…Thus, specific functions were identified that may differ between intestinal tissues of the sexes. From whole worm studies, female worm associated lipid transport functions were also reported in Trichuris globulosa (Sarwal et al 1989). …”
Section: Discussionmentioning
confidence: 98%
“…These variations might occur due to the availability of food materials, which is influenced by the food habit of the host, in the different microhabitat of the parasites. Key enzymes of lipid biosynthesis have been observed in Haemonchus contortus (Kapur and Sood 1987), Trichuris globulosa (Sarwal et al 1989) and A. galli (Aggarwal et al 1989). A. galli, being capable of synthesizing lipids into other forms, absorbs less TL than cestode.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently it would not be surprising to discover that some parasitic nematode lineages have evolved the pathways necessary to produce host-metabolism regulating molecules from steroids and/or other precursors. Lipid metabolism has been documented in Trichurisglobulosa (see Sarwal, Sanyal& Khera, 1989) and 0. gibsoni (see Maloney & Semprevivo,199 Korant & Knight, 1986). It is conceivable (although we concede highly speculative at this stage) that nematode parasites have evolved similar molecules through which they might downregulate host immunity.…”
Section: Immunomod~lationmentioning
confidence: 99%